Is 24, 25-dihydroxycholecalciferol a calcium-regulating hormone in man?. Issue 6124 (27th May 1978) - Kanis, J A; Cundy, T; Bartlett, M; Smith, R; Heynen, G; Warner, G T; Russell, R G
Abstract : Small doses (1-10 microgram daily) of 24, 25-dihydroxycholecalciferol (24, 25-(OH)2D3), a renal metabolite of vitamin D of uncertain function, increased intestinal absorption of calcium in normal people and in patients with various disorders or mineral metabolism, including anephric subjects. In five of six patients studied, calcium balance increased, but, unlike 1, 25-dihydroxycholecalciferol, 24, 25-(OH)2D3 did not increase plasma or urinary calcium concentrations. These results suggest that 24, 25-(OH)2D3 may be an important regulator of skeletal metabolism in man with potential value as a therapeutic agent.